Comparison of trauma patients with typical-atypical rib fractures - Cakmak, Muharrem (Bayrakol Medical Publisher, 2023)
Aim: Morphologically, ribs are classified as typical or atypical. While typical ribs are the 3-9th ribs, atypical ribs are the 1st, 2nd, and 10-12th ribs. There are several studies on rib fractures. However, no specific studies and comparisons have been reported on rib fractures according to the calcifications of the ribs. In our study, we aimed to share the results of trauma patients with typical-atypical rib fractures. Material and Methods: According to the morphological features of the broken ribs, the patients were divided into two groups: Group 1 (patients with typical rib fractures; 322) and Group 2 (patients with atypical rib fractures; 160). The results were evaluated. p<0.05 was considered significant. Results: According to the demographic distribution of the patients, the male gender was more significant in Group 1 compared to Group 2 (p<0.05). However, there was no significant difference between the groups in terms of the number of patients who died and localization (p>0.05). In terms of concomitant pathologies, pneumomediastinum, contusion, and flail chest development were statistically significant in Group 1 patients compared to Group 2 (p<0.05). The mean CWIS of Group 1 was found to be significant compared to Group 2 (p<0.05). Discussion: According to our study, in terms of concomitant pathologies, pneumomediastinum, contusion, and flail chest development in typical rib fractures were more common in patients with atypical rib fractures. Although trauma scores were generally higher in Group 2 than in Group 1, they were not significant in patients with typical-atypical rib fractures except for CWIS. Especially in patients with a high CWIS, surgical treatment can be performed depending on the condition of the concomitant organ injuries.
Keywords: Ribs; Fractures; Thorax; Trauma